2017
DOI: 10.1111/tpj.13616
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptome analysis of nodules of two Mesorhizobium–chickpea associations with differential symbiotic efficiency under phosphate deficiency

Abstract: Phosphate (Pi) deficiency is known to be a major limitation for symbiotic nitrogen fixation (SNF), and hence legume crop productivity globally. However, very little information is available on the adaptive mechanisms, particularly in the important legume crop chickpea (Cicer arietinum L.), which enable nodules to respond to low-Pi availability. Thus, to elucidate these mechanisms in chickpea nodules at molecular level, we used an RNA sequencing approach to investigate transcriptomes of the nodules in Mesorhizo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 66 publications
0
43
0
Order By: Relevance
“…In addition to the above abiotic stressors, Pi deficiency is known to be a major limitation for symbiotic N 2 fixation, and hence can reduce legume crop productivity (Kleinert, Thuynsma, Magadlela, Benedito, & Valentine, ; Nasr Esfahani et al, ). Recently, Nasr Esfahani et al () investigated transcriptome changes in the nodules of Mesorhizobium ciceri CP‐31‐( Mc CP‐31)‐chickpea and Mesorhizobium mediterraneum SWRI9‐( Mm SWRI9)‐chickpea associations under Pi‐deficient and Pi‐sufficient conditions.…”
Section: Transcriptome Dynamics In Legumes Under Abiotic Stressesmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition to the above abiotic stressors, Pi deficiency is known to be a major limitation for symbiotic N 2 fixation, and hence can reduce legume crop productivity (Kleinert, Thuynsma, Magadlela, Benedito, & Valentine, ; Nasr Esfahani et al, ). Recently, Nasr Esfahani et al () investigated transcriptome changes in the nodules of Mesorhizobium ciceri CP‐31‐( Mc CP‐31)‐chickpea and Mesorhizobium mediterraneum SWRI9‐( Mm SWRI9)‐chickpea associations under Pi‐deficient and Pi‐sufficient conditions.…”
Section: Transcriptome Dynamics In Legumes Under Abiotic Stressesmentioning
confidence: 99%
“…In addition to the above abiotic stressors, Pi deficiency is known to be a major limitation for symbiotic N 2 fixation, and hence can reduce legume crop productivity (Kleinert, Thuynsma, Magadlela, Benedito, & Valentine, ; Nasr Esfahani et al, ). Recently, Nasr Esfahani et al () investigated transcriptome changes in the nodules of Mesorhizobium ciceri CP‐31‐( Mc CP‐31)‐chickpea and Mesorhizobium mediterraneum SWRI9‐( Mm SWRI9)‐chickpea associations under Pi‐deficient and Pi‐sufficient conditions. Transcriptome analysis showed that Pi deficiency caused changes in the expression of more genes in Pi‐deficiency‐more‐sensitive Mm SWRI9‐induced nodules than in Pi‐deficiency‐less‐sensitive Mc CP‐31‐induced nodules, demonstrating distinct changes in gene expression in the two Mesorhizobium species in response to Pi deficiency (Nasr Esfahani et al, ).…”
Section: Transcriptome Dynamics In Legumes Under Abiotic Stressesmentioning
confidence: 99%
See 3 more Smart Citations